Functionalized carbon nanotubes for potential medicinal applications - Zhang, Yi (Drug Discov Today, 2010)
Functionalized carbon nanotubes display unique properties that enable a variety of medicinal applications, including the diagnosis and treatment of cancer, infectious diseases and central nervous system disorders, and applications in tissue engineering. These potential applications are particularly encouraged by their ability to penetrate biological membranes and relatively low toxicity.